Neisseria gonorrhoeae NspA Induces Specific Bactericidal and Opsonic Antibodies in Mice - Li, Guocai (American Society for Microbiology, 2011)

(untitled)
Neisseria gonorrhoeae surface protein A (NspA) is a highly conserved gonococcal antigen. To explore the potential of NspA in vaccine development against gonorrhea, BALB/c mice were immunized with pcNspA containing the NspA gene from N. gonorrhoeae strain WHO-A via intramuscular (i.m.) injection, intranasal (i.n.) immunization, or intravaginal (i.vag.) immunization. Following the last DNA immunization, mice were boosted with recombinant NspA (rNspA). Enzyme-linked immunosorbent assays (ELISAs) indicated that all immunized mice generated measurable NspA-specific IgG and IgA in serum and secretory IgA (sIgA) in vaginal wash fluids. The antisera had bactericidal and opsonic activities. These data demonstrated that NspA induced antibodies with antigonococcal activity.